Upaya Guru PAI dalam Memotivasi Belajar Siswa Kelas XII : (studi di perguruan tinggi di ma al-barokah ) - nur khosiah; Abdurrohman wahid; Abdurrohman sholeh (STAI Attanwir Bojonegoro, 2022)
The spirit of learning towards students is very important for the success of teaching and learning activities, because the success or failure of the teaching and learning process depends on the enthusiasm possessed by students. It is a challenge for all teachers to have students who lack a strong interest in learning and continue to college. To address this, PAI teachers at MA Al-Barokah use various strategies so that their students have a strong interest in learning and continue to higher education. In this study using descriptive qualitative methods. Data collection techniques are observation, interviews, documentation. The results of the study describe the situation of the students' enthusiasm for learning at MA Al-Barokah is quite good, but the factors that are quite influential in interest in learning and studying at college are parents and the environment where they live. While the efforts of PAI teachers in motivating the learning of class XII students to continue to a higher level include providing non-observing material, using creative and fun methods, giving gifts to make them more enthusiastic about learning, using play while learning methods, playing an active role in the learning process. teach and organize and design learning methods efficiently, effectively and creatively in the teaching and learning process.